Strain-Engineered Oxygen-Modified Nickel Telluride/Nickel Oxide Heterostructures for Bifunctional Alkaline Water Electrocatalysis - Shin, Seunghun; Cho, Iaan; Han, Sun Kyung; Heo, Jaewon; Han, Junhwi; Jeon, Hotae; Lee, Jaehyun; Cho, Min Kyung; Preston, Daniel J.; Kim, In Soo; Shong, Bonggeun; Lee, Won-Kyu (American Chemical Society, 2025)
We present a strain-engineering strategy for oxygen-modified nickel telluride/nickel oxide heterostructures capable of enabling bifunctional alkaline water electrolysis with performance surpassing Pt and IrOx benchmarks. The heterostructures are synthesized via electrochemical Te dissolution and mild oxidation of mechanically exfoliated NiTe2, followed by controlled strain induction through substrate buckling. Atomic-scale simulations and spectroscopic analyses indicate that Te-vacancy/O-substituted NiTe2 domains promote oxygen-intermediate spillover between adjacent active sites, reducing OER overpotentials. In parallel, strained NiTe2 domains facilitate hydrogen-intermediate transfer to NiO containing Ni vacancies, leading to accelerated HER kinetics and near-thermoneutral hydrogen adsorption. Strain modulation adjusts the electronic structure and increases active-site density, enabling stable operation at industrial-level current densities (>1 A cm–2). These findings illustrate how defect chemistry coupled with strain engineering can be utilized to develop high-performance, earth-abundant bifunctional electrocatalysts.